2009
DOI: 10.4049/jimmunol.0901541
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Hyperresistinemia in Severe Acute Streptococcal Infections

Abstract: The concept of neutrophil activation and degranulation as important contributors to disease pathology in invasive group A streptococcal infections has recently been emphasized. This study focuses on two of the most severe streptococcal manifestations, toxic shock syndrome and necrotizing fasciitis, and the newly described proinflammatory molecule resistin, known to derive from adipocytes and monocytes. We demonstrate for the first time that these conditions are characterized by hyperresistinemia in circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…However, increases in the level of resistin, a proinflammatory peptide derived from neutrophils, have been correlated with disease severity in both NSTIs and septic shock (98). It is known that degranulation events in neutrophils lead to the release of azurophilic and specific granules into the extracellular space, exposing the surrounding tissue to toxic enzymes and antimicrobial peptides (99).…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in the level of resistin, a proinflammatory peptide derived from neutrophils, have been correlated with disease severity in both NSTIs and septic shock (98). It is known that degranulation events in neutrophils lead to the release of azurophilic and specific granules into the extracellular space, exposing the surrounding tissue to toxic enzymes and antimicrobial peptides (99).…”
Section: Discussionmentioning
confidence: 99%
“…In a knock-out mouse model it has been demonstrated that the lack of resistin protects against diet-induced insulin resistance and type 2 diabetes mellitus [40]. Elevated resistin serum levels have been found in critically ill patients with significantly higher concentrations in sepsis than in non-sepsis patients and peak values in septic shock [37,41]. Likely, resistin seems to act as an acute-phase protein and might be part of the systemic inflammatory response, as it has been correlated to IL-6, IL-10, TNF-α, C-reactive protein and procalcitonin [42].…”
Section: Resistinmentioning
confidence: 98%
“…Human resistin is mainly derived from macrophages and neutrophils as recently reported [37] and not from adipocytes (like in mice [38]) and has been implicated in glucose metabolism and insulin sensitivity. It is named for mediating resistance to insulin through the exacerbation of the adipose tissue inflammation in humans [39].…”
Section: Resistinmentioning
confidence: 99%
“…Besides its direct proinflammatory effects, IL-6 also increases the CRP production by the liver and the expression of resistin on peripheral blood mononuclear cells [14]. As mentioned before, resistin has emerged as a powerful proinflammatory mediator and its role in both acute and chronic inflammatory processes has been described [7,15]. In adult patients with sepsis, resistin was implicated as an effective biomarker of sepsis severity and as a predictor of mortality of critically ill adult patients.…”
mentioning
confidence: 99%
“…In rates, resistin is secreted only by adipocytes, whereas in humans, other cells can secret it as muscle cells, and macrophages [5]. Studies in adult patients with sepsis established that resistin is secreted by the macrophages and neutrophils in response to acute bacterial infection [6,7,8]. In addition, it has been reported that resistin levels is correlated with the severity and duration of the disease *Coresponding Author: Heba Mostafa Ahmed, Beni-Suef University, Faculty of Medicine, Depatrement of Pediatrics, Egypt E-mail: heba_most@yahoo.com in patients with sepsis and septic shock [8].…”
Section: Introductionmentioning
confidence: 99%